Profil Penanganan Pangan, Pola Konsumsi dan Status Gizi Keluarga: Studi Kasus di Kecamatan Kopo, Serang, Banten - Sigit Purwonugroho; Nurheni Sri Palupi; Siti Nurjanah (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2018)
Household food handling practices is important to ensure safe food consumed by family members. Consumption of safe food is needed to support optimal nutritional status. The Indonesia Food and Drug Agency (2015) data showed that foodborne illness in families i.e 40.98%. This indicates a high food safety risk in household processed food, therefore it is necessary to study and evaluate the food handling practices in family. The purpose of this study was to provide data of food handling practices, consumption pattern and family nutrition status in Kopo, Serang, Banten. The study involved 100 respon-dents (family) consisting of father, mother and two children. Data were obtained through questionnaire, surveys and physical observation of respondents. The design of this study was cross-sectional and descriptive analysis. The assessment suggested that 74% of families have been implemented good food handling practices. Percentage of good nutritional status of each family member includes father (70%), mother (83%) and children (95%). 76% respondents consume six or more groups of food sources such as carbohydrates, animal and plant proteins, fats, fruits and vegetables while some other respondents lacked of animal protein and fruit consumption.